Extracellular terpenoid hydrocarbon extraction and quantitation from the green microalgae Botryococcus braunii var. Showa - Eroglu, Ela; Melis, A. (Elsevier BV, 2010)
Mechanical fractionation and aqueous or aqueous/organic two-phase partition approaches were applied for extraction and separation of extracellular terpenoid hydrocarbons from Botryococcus braunii var. Showa. A direct spectrophotometric method was devised for the quantitation of botryococcene and associated carotenoid hydrocarbons extracted by this method. Separation of extracellular botryococcene hydrocarbons from the Botryococcus was achieved upon vortexing of the micro-colonies with glass beads, either in water followed by buoyant density equilibrium to separate hydrocarbons from biomass, or in the presence of heptane as a solvent, followed by aqueous/organic two-phase separation of the heptane-solubilized hydrocarbons (upper phase) from the biomass (lower aqueous phase). Spectral analysis of the upper heptane phase revealed the presence of two distinct compounds, one absorbing in the UV-C, attributed to botryococcene(s), the other in the blue region of the spectrum, attributed to a carotenoid. Specific extinction coefficients were developed for the absorbance of triterpenes at 190 nm (e = 90 ±5mM-1 cm-1) and carotenoids at 450 nm (e = 165 ± 5 mM-1 cm-1) in heptane. This enabled application of a direct spectrophotometric method for the quantitation of water- or heptane-extractable botryococcenes and carotenoids. B. braunii var. Showa constitutively accumulates ~30% of the dry biomass as extractable (extracellular) botryococcenes, and ~0.2% of the dry biomass in the form of a carotenoid. It was further demonstrated that heat-treatment of the Botryococcus biomass substantially accelerates the rate and yield of the extraction process. Advances in this work serve as foundation for a cyclic Botryococcus growth, non-toxic extraction of extracellular hydrocarbons, and return of the hydrocarbon-depleted biomass to growth conditions for further product generation. © 2009 Elsevier Ltd. All rights reserved.